ADMINISTRATIVE FUNCTION OF LOCAL GOVERNANCE IN GODAWARI MUNICIPALITY, LALITPUR, NEPAL - Bhattarai, Naba Raj; Pasa, Rajan Binayek (International Journal of Research -GRANTHAALAYAH, 2021)
This study explains administrative functions of local governance in Godavari municipality of district. For that purpose, the quantitative research approach and instrumental case study in multi-site research design has been applied. The required data were collected from 234 respondents (Administrative staffs 12 elected representatives and local intellectuals 30 and service receivers 192) through institutional survey and exit poll survey techniques selected by , cluster and stratified random sampling methods. This study found that average value of administrative functions related variables was 1.88 to 2.14 or perceptions of the respondents over studied variables felled between "strongly agree and agree". And the average value of quality of administrative functions related variables also found 1.96 to 2.76 (strongly agree and nearer to neutral" with 0.60 to 1.44 standard deviation and 0.15 standard errors for the . However, Pearson correlation coefficient between administrative function index (maximum 35, minimum 7, mean 24.08 and standard deviation 3.41) and quality of administrative function index (maximum 28, minimum 4, mean 14.26 and standard deviation 2.57), r= 0.88, > r2= 0.05 and p=0.00 found significant (strong positive correlation)